2015
DOI: 10.1155/2015/547925
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Natural Phenolic Compounds onAspergillus parasiticusGrowth

Abstract: Considering the impact ofAspergillusspecies on crops, it appears to be highly desirable to apply strategies to prevent their growth, as well as to eliminate or reduce their presence in food products. For this reason, the aims of this investigation were to evaluate the effects of ten natural phenolic compounds on theAspergillus parasiticusgrowth and to determine which physicochemical properties are involved in the antifungal activity. According to the results of minimum inhibitory concentration (MIC) values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
(41 reference statements)
1
23
0
3
Order By: Relevance
“…Pizzolitto et al [22] also screened strains of the filamentous fungus Aspergillus parasiticus using the phytochemicals: thymol, carvacrol, eugenol, isoeugenol, creosol, m-Creosol, p-Creosol, o-Cresol and phenol. In this study, they found that isoeugenol had a MIC of 206 μg/mL, which was lower than those found in the other compounds tested, showing its potency against the microorganism, including carvacrol.…”
Section: Resultsmentioning
confidence: 99%
“…Pizzolitto et al [22] also screened strains of the filamentous fungus Aspergillus parasiticus using the phytochemicals: thymol, carvacrol, eugenol, isoeugenol, creosol, m-Creosol, p-Creosol, o-Cresol and phenol. In this study, they found that isoeugenol had a MIC of 206 μg/mL, which was lower than those found in the other compounds tested, showing its potency against the microorganism, including carvacrol.…”
Section: Resultsmentioning
confidence: 99%
“…The radios of the colonies were plotted against time, and a linear regression applied in order to obtain the growth rate as the slope of the line. The effect of each ketone compound on Lag phase for growth, was defined as the time (days) in which each colony reaches 5 mm of diameter [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Modern strategies of biological control of pests are being investigated as alternatives to synthetic pesticides; monoterpenes found mainly as components of essential oils of plants are an alternative. Previous studies reported bioactivities (antifungal, insecticidal and repellence) of terpenes with different structural groups on stored grain pests, with ketones being the most bioactive [ 14 , 15 , 16 , 17 ]. However, little is known about the bioactivity of natural ketone compounds against biotrophic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…According to Pizzolitto et al reported the ability of the organic compounds to perturb the cell membrane integrity. Thus, the mechanism depends on the organic ability to affect the function of cellular lipoprotein membranes 17 . Moreover, refractivity index and molar volume are related to the antifungal effect, indicating that specific interactions between the phenolic compounds and the target receptor could be implicated in the inhibitory activity.…”
Section: Lichen Powder Extractmentioning
confidence: 99%